Tailoring the morphology and surface plasmon coupling of BiVO4 toward efficient visible-light degradation of antibiotic pollutants - Thinh B. Le; Van M. Dinh; Phuong T.M. Ha; Dat H. Nguyen; Thien P. Nguyen; Nhi T. Y Nguyen; Tuan A. Nguyen; YB.N. Tran; Kim-Ngan N. Phan; Hiep Q. Ha; Dai-Viet N. Vo (Environmental Research, 2026)

Assessment of Road Dust Heavy Metal Pollution and Health Risk in Urban-Industrial Transition Zones: Implications on Environmental Management for Emerging Cities - Quoc Ba Tran; Ly Sy Phu Nguyen; Nguyen Xuan Cuong; Tinh H. T. Nguyen; Tran Xuan Vu; Le Quoc Hau; Nguyen Duy Dat (International Journal of Environmental Research, 2025)

Current conservation status of Germain’s langur (Trachypithecus germaini) in Vietnam - Bang Van Tran; Minh Anh Nguyen; Dat Quoc Nguyen; Quan Bich Thi Truong; Andie Ang; Herbert H. Covert; Duc Minh Hoang (Primates, 2017)

Bioeconomics of mud crab, Scylla paramamosain , culture in Vietnam - Elizabeth H. Petersen; Truong H. Phuong; Nguyen Van Dung; Pham T. Giang; Nguyen K. Dat; Vu A. Tuan; Tran V. Nghi; Brett D. Glencross (Reviews in Aquaculture, 2013)
The results of bioeconomic analysis informed by a survey of 80 small‐scale mud crab farmers in Vietnam are presented in this paper. Mud crab farming in Vietnam is profitable, with net revenue being approximately 135 and 41 million VND/year (USD 7000–USD 2100 per year) in the central and southern regions, respectively. Profitability was significantly higher in the centre compared with the north, as almost three times the biomass is harvested in the centre compared with the south (in turn, due to higher aquaculture area and survival rates). The benefit–cost ratio (the ratio between total revenue and total costs) is 3.55 in the centre and 1.97 in the south. The crabs are fed almost exclusively on low‐value finfish in the centre and the south. Feeding rates were found to be low, with 95% of biomass gain coming from natural feed in the environment rather than supplementary feeding by the farmer. If pellets are to be adopted widely by mud crab farmers, negative perceptions regarding the poor adaptability of mud crab to pellets (northern farmers only), relatively slow growth rates compared with low‐value finfish and lack of availability of pellets need to be overcome.